Combined effects of ocean warming and acidification on the larval stages of the European abalone Haliotis tuberculata. (February 2022) - Kavousi, Javid; Roussel, Sabine; Martin, Sophie; Gaillard, Fanny; Badou, Aicha; Di Poi, Carole; Huchette, Sylvain; Dubois, Philippe; Auzoux-Bordenave, Stéphanie
Abstract: This study examined the physiological responses of the larval stages of Haliotis tuberculata, an economically important abalone, to combined temperature (17 °C and 19 °C) and pH (ambient pH and −0.3 units, i.e., +200% increase in seawater acidity) in a full factorial experiment. Tissue organogenesis, shell formation, and shell length significantly declined due to low pH. High temperature significantly increased the proportion of fully shelled larvae at 24 h post-fertilization (hpf), but increased the proportion of unshelled larvae at 72 hpf. Percentage of swimming larvae at 24 hpf, 72 hpf and 96 hpf significantly declined due to high temperature, but not because of low pH. Larval settlement increased under high temperature, but was not affected by low pH. Despite the fact that no interaction between temperature and pH was observed, the results provide additional evidence on the sensitivity of abalone larvae to both low pH and high temperature. This may have negative consequences for the persistence of abalone populations in natural and aquaculture environments in the near future. Highlights: Combined impacts of ocean acidification and warming on the larvae of the European abalone were investigated. No interactive impact of temperature and pH was recorded. Tissue organogenesis, shell formation, and shell length significantly declined due to low pH. High temperature significantly increased the proportion of fully shelled larvae at 24 hpf, but increased the proportion of unshelled larvae at 72 hpf. High temperature increased the settlement rate of the larvae.